Improved MMSE Scheme in Cooperative Base Station Systems - A., Hameed (Asian Journal oflnformation Technology, 2014)
This study addresses minimum mean square error scheme used with asynchronous interference mitigation in cooperative base stations. The asynchronous transmission is considered owing to the dissimilar transmission times between the base station and mobile stations. Fwthermore, the channel quantization errors due to channel quantization are taken into accollllt. The suggested model is resilient to asynchronous interference and channel quantization errors associated with base station cooperative systems. The developed scheme outperforms the conventional ones formd in literature as demonstrated.